Die Kopplung des Windes in der oberen Troposphäre mit plötzlichen Stratosphärenerwärmungen - Hänsch, Martje (2020)
Sudden stratospheric warmings (SSWs) are phenomenons of rising temperatures in the polar stratosphere combined with a breakdown of the polar vortex. They occur mainly in the Northern Hemisphere and are often followed by anomalies in the tropospheric circulation. SSWs can be classified in those events that have an impact on the tropospheric circulation (dSSW) and those that do not (nSSW). Jet streams are ribbons of high wind speeds in the height of the tropopause and are crucial for the weather in the midlatitudes. They are affected by SSWs as they become weaker and are displaced equatorwards. In this study anomalies of jet stream position and strength are analysed during SSWs. It is tested whether there are different impacts when differing between dSSWs and nSSWs. In addition, sea ice content (SIC) and sea surface temperature (SST) are also studied during SSWs, because they are known as drivers of jet stream anomalies. Previous studies investigated influences of SST anomalies in the Pacific and of SIC anomalies on the stratospheric polar vortex and on SSWs. These influences, regarding the distinction of dSSW and nSSW, are widely unexplored yet. First, jet stream climatologies and trends from previous literature are reproduced with ERA5 reanalysis data. Then, composites for a time period of ± 90 days around the SSW central date are made. In the results a decrease in the strength of the jet stream and an equatorward shift are seen for dSSWs. For nSSWs only weak and not significant anomalies appear. In the lower-tropospheric circulation, changes appear only in the Atlantic sector and over Europe after dSSWs and little changes are seen after nSSWs. SST anomalies in the Pacific display a clear pattern before and during nSSWs with colder temperatures in the East Pacific and northernmost Pacific and with warmer temperatures in the Western Pacific and central North Pacific. In the Atlantic less anomalies are found. During dSSWs in all oceans only little anomalies are seen. SIC anomalies in the Barents-Kara Sea show ...